Numerical Simulation of Supersonic Overexpanded Jet from 2-D Convergent-Divergent Nozzle - Srivastava, Shantanu (International Journal of Integrated Engineering, 2018)
The present study focuses on the numerical investigation of the Mach 1.86 supersonic jet from the 2-D convergent-divergent nozzle for NPRs 4 to 6 with a step size of one, covering the overexpanded and the near correct expansion conditions. The computational model is constructed into design modular of ANSYS 16.0 workbench. The structured grids are generated into the ICEM module of the ANSYS workbench and the fluid flow analysis, on the modelled part is done by FLUENT solver. The extent of jet mixing is identified by plotting non-dimensional total pressure, along the jet centerline, with respect to the non-dimensional distance downstream of the nozzle exit and along the jet centerline. Also the Mach contours are plotted for different NPRs indicating, the number of shock cells and the variation of the shock strength with respect the change in the NPR due to the prevailing adverse pressure gradient at the nozzle exit.